Front Cover: Improved Synthesis of ortho‐Phenylene‐bridged Cyclic Tetrapyrroles and Oxidative Fusion Reactions Toward Substituted Tetraaza[8]circulenes (Chem. Asian J. 6/2021). Issue 6 (18th February 2021) - Morimoto, Yuki; Chen, Fengkun; Matsuo, Yusuke; Kise, Koki; Tanaka, Takayuki; Osuka, Atsuhiro
Abstract : Heteroatom‐embedded [8]circulenes have emerged as novel functionalized heteronanographenes that show various promising functions such as bright fluorescence, charge transporting, and redox reactivities. An improved synthetic method of cyclic tetrapyrrole precursors has been developed by utilizing a reverse coupling strategy, from which opposite‐type tetrasubstituted tetraaza[8]circulenes have been obtained by a fold‐in oxidative fusion reaction. The substituent effects were comprehensively studied by XRD analysis, UV/Vis and fluorescence spectroscopy, and cyclic voltammetry. More information can be found in the Full Paper by Takayuki Tanaka et al.